AB0878 Efficacy and Safety of Rumalaya Forte to Patients with Hand Osteoarthritis (HOA). (9th June 2015) - Patru, S.; Marcu, I.R.; Matei, D.; Bighea, A.C.
Abstract : Background: Although Paracetamol and NSAIDs are commonly prescribed for the patients with osteoarthritis, gastrointestinal, hepatic and renal toxicity limit their usage. Herbal medicine is wide spread and presents a large source that might serve for development of novel drugs. Rumalaya Forte (RF) is one such poly herbal formulation prescribed to osteoarthritic patients for years. Several clinical studies have been undertaken with Rumalaya forte. Objectives: This randomized, double-blinded, placebo controlled study tried to evaluate the clinical efficacy and safety of Rumalaya forte to patients suffering from HOA. Methods: All the patients with clinical and radiological evidence of HOA were randomized into 2 groups of 20 patients each (Rumalaya forte and acetaminophen groups). Clinical evaluation was done at baseline and after the completion of six weeks, using a visual analogue scale for pain and morning stiffness and a hand function test with short administration time, the Moberg Picking-Up Test (MPUT). Were recorded all the adverse events. Results: The treatment groups were comparable in terms of baseline characteristics. After 6 weeks of treatment RF decreased the pain by 31.7% and acetaminophen by 25.8%. Morning stiffness decreased by 37.2% in RF group and by 30.5% in the other treatment group. RF was significantly superior to acetaminophen in improving hand function (better times to 6 weeks MPUT, 12.3 sec.vs 14.8 sec.). There were no clinically significant adverse events in both groups. Conclusions: RF was more effective as acetaminophen in improving hand osteoarthritis symptoms and increased joint mobility and strength to HOA patients. References: Clinical evaluation of the efficacy of JT-2000* in the management of osteoarthritis: A double-blind placebo-controlled trial. Upadhyay, L., Tripathi, K. Medicine Update (2004): (11), 10, 31. Evaluation of the efficacy and safety of JT-2000* in Osteoarthritis: A randomized controlled clinical trial. Khare, K.D., Rahul Khare. Indian Journal of Clinical Practice (2004): (14), 10, 42. Evaluation and Comparative Clinical Efficacy and Safety of Rumalaya Forte in Patients Suffering from Osteoarthritis of the Knee. Nirbhay Srivastava, R Sadh, BK Jain. Indian Journal of Clinical Practice July 2005. Disclosure of Interest: None declared